Ohm Krüger: Context, Appropriation and Irony. Issue 4 (2nd October 2021) - Titlestad, Michael
ABSTRACT: Ohm Krüger premièred in Berlin in 1941 and was widely praised by audiences, critics and the Nazi high command. Joseph Goebbels, the Reich's Minister of Propaganda, instituted a special award to honour the film, Film der Nation (Film of the Nation), and it was pronounced reichswichtig (important to the state). Ohm Krüger places in parallel the Boer War (1899–1902) 1 and the rise of German National Socialism. Presenting these histories as contiguous generates a series of ironies that undermine the film's propagandist intentions. This is most striking in the concentration camp sequences at its climax. In order to consider the ways in which these scenes are at cross purposes with the ideological logic of the film, this article contextualises Ohm Krüger's production, reviews the dynamics of its appropriation of the Boer cause, and dwells on its self-subversion. The argument concludes that totalitarianism is based, in part, on inculcating a mindset in its subjects consisting of their capacity to overlook contradictions between hegemony and reality.